Development of interactive multimedia for Arabic vocabulary learning through Android applications - Robi'ah, Siti; Shodiq, Muhammad Jafar; Tukimin, Tukimin; Astuti, Henni (Jurnal Internasional Pendidikan Bahasa Arab, 2023)
This study aims to develop Android -based interactive multimedia in learning Arabic vocabulary so that students can use it as an independent learning resource that can be accessed anytime and anywhere and can be used by teachers to deliver Arabic vocabulary material effectively and efficiently. This research uses research and development methods, with ADDIE development model. The result of this research is to produce Android-based Arabic vocabulary learning media products developed with construct 2 software containing Arabic language learning for classes V MIN 2 South Lampung and V MI Ma'arif Nu South Lampung. To test the feasibility of Android-based interactive multimedia by validating products made to a team of experts and obtained an average percentage score of 80.56% by media experts, 83.89% by material experts. Then the product attractiveness test was assessed by students and obtained an assessment of 90.72% with the criteria of "very feasible". So the update that researchers made with previous researchers is a product packaged in the form of an Android-based interactive multimedia application in learning Arabic vocabulary so that students can learn it anywhere and anytime, both independently and in class.